The Effect of Bitter Wormwood (Artemisia Absinthium L.) on The Chemical Composition of Honey - Furqat qizi, Karilova Marjona; Shavkat qizi, Xo’jayeva Komila; Buriyevich, Ibragimov Furqat; Rayimjonovna, Dildora Nasimova (American Journal of Biodiversity, 2026)
This article presents a comprehensive literature-based analysis of the influence of bitter wormwood (Artemisia absinthium L.) on the chemical composition of honey. The study emphasizes variations in the primary constituents of honey, including carbohydrates, enzymes, organic acids, mineral elements, and biologically active compounds, depending on the botanical origin of nectar. The findings indicate that honey derived from A. absinthium nectar is characterized by elevated levels of phenolic compounds, flavonoids, and essential oils. These compositional changes are associated with enhanced antioxidant capacity, antimicrobial activity, and overall therapeutic potential of the resulting honey.